Spinal Manifestation of Sickle Cell Disease. A Report On 35 Patients with Literature Review - Shalal, Furat Hassan; Hamdan, T. A; Chasib, Raed Jasim; F. Lui, Darren (Clinical Medicine And Health Research Journal, 2024)
Background: Sickle cell disease is a hereditary hemoglobinopathy affecting the spine in a wide range of pathology. Despite the several pathological involvements, some patients remain asymptomatic even with positive imaging findings. Objectives: Theme of this study is to report the various pathological disorders involving the spine of patients with sickle cell disease in Basra “south of Iraq” Patients and method: 35 Homozygous and heterozygous sickle cell patients were included in this study. 22 Males and 13 females, their age range from 6 to 69 years they were evaluated clinically, and also by laboratory imaging studies like plain radiography, computerized tomography, magnetic resonance imaging and mineral bone density “DEXA scan “ Results: 54% of the patients were homozygous, and the remaining were heterozygous, 66% of them were asymptomatic, back pain was the complaint in 60% while spine tenderness was reported in 40%, 31% had tenderness in the sacroiliac region and only 6% had neurological claudication and focal neurological deficit. Biconcave vertebra was confirmed in 72% of the patients and mainly localized in the lumbar Spine, MRI findings of vertebral infarction were observed in 58% of the studied patients while sacroiliac joint changes appeared in 60%, 60% of those who had DEXA scan showed low mineral bone density in the lumbar spine Conclusion: Sickle cell disease involve the whole Spine in a wide range of pathological process, some show clinical symptoms, and some remain asymptomatic in spite of changes. The structural changes are more obvious in the homozygous group (55) the lumber spine is dominantly involved, disc prolapse, and neurological deficit is rare while the low mineral changes is common. We did not report a case of spondylodiscitis in this series, though it is very much expected, so routine screening of the spine in sticklers is mandatory